The Theory of Positive Discrimination in Tax Matters for Migrants and Refugees in Peru: Legal Analysis of Vulnerability Status - Echevarria Rojas, Melannie Soila (2024)
The research topic focuses on individuals who, out of fear of persecution, have fled their country of origin and deserve protection within the possibilities of the host country, as a general legal principle among nations. The precarious situation of migrants, where their rights are violated for various reasons, deserves attention from projects aimed at improving our tax legal system. This attention is not only for the observance of their fundamental rights but also due to the risk of harm and conditions of inequality. This finds support in tax principles, especially in the principle of tax equality that seeks to ensure fair treatment. Through qualitative study, we have been able to highlight certain aspects of vulnerability in migrants that could justify positive discrimination in the taxrelated issue presented. The concept of positive discrimination aims to justify the implementation of public policies oriented towards granting preferential treatment to a specific social group. In this case, migrants and refugees who are affected by the 30 % retention on their minimum vital remuneration due to their nonresident status.